Uppmärksamhed - Kan Simone Weil bidra till feministisk etik? - Ulla Holm (The Royal Danish Library, 1999)
Simone Weil was certainly no feminist. Still her concept of attention may be helpful for feminists who want to go beyond some current orthodoxies, on the one hand modern theoretical-juridical models of ethics and on the other an impasse in feminist ethics between gynocentric and humanist ethical approaches where such phenomena as care and justice risk to become opposites. These phenomena need alternative moral understandings or frameworks and Weil provides at least a beginning to an open-ended alternative. The genesis of her concept of attention is traced from a material grounding and focus on natural necessities to her mature conceptual ecology and focus on normative necessities in human relations and in the very concept of a human being. An attentive mind can discern this normativity and allow refletion to move beyond partial perspectives. In suh a conception justice and care are not opposites, but rather presuppose each other.